Putting desire on a budget: dopamine and energy expenditure, reconciling reward and resources - Beeler, Jeff A.; Frazier, Cristianne R.; Zhuang, Xiaoxi (Frontiers in Integrative Neuroscience, 2012)
Accumulating evidence indicates integration of dopamine function with metabolic signals, highlighting a potential role for dopamine in energy balance, frequently construed as modulating reward in response to homeostatic state. Though its precise role remains controversial, the reward perspective of dopamine has dominated investigation of motivational disorders, including obesity. In the hypothesis outlined here, we suggest instead that the primary role of dopamine in behavior is to modulate activity to adapt behavioral energy expenditure to the prevailing environmental energy conditions, with the role of dopamine in reward and motivated behaviors derived from its primary role in energy balance. Dopamine has long been known to modulate activity, exemplified by psychostimulants that act via dopamine. More recently, there has been nascent investigation into the role of dopamine in modulating voluntary activity, with some investigators suggesting that dopamine may serve as a final common pathway that couples energy sensing to regulated voluntary energy expenditure. We suggest that interposed between input from both the internal and external world, dopamine modulates behavioral energy expenditure along two axes: a conserve-expend axis that regulates generalized activity and an explore-exploit axes that regulates the degree to which reward value biases the distribution of activity. In this view, increased dopamine does not promote consumption of tasty food. Instead increased dopamine promotes energy expenditure and exploration while decreased dopamine favors energy conservation and exploitation. This hypothesis provides a mechanistic interpretation to an apparent paradox: the well-established role of dopamine in food seeking and the findings that low dopaminergic functions are associated with obesity. Our hypothesis provides an alternative perspective on the role of dopamine in obesity and reinterprets the ‘reward deficiency hypothesis’ as a perceived energy defici